Faktor-Faktor yang Mempengaruhi Kualitas Permukiman Pasca Gempa Bumi Di Kecamatan Pleret Kabupaten Bantul - Sri Rum Giyarsih; Syarifah Aini Dalimunthe (TATALOKA, 2013)
This research was conducted in Pleret Subregency, Bantul Regency, specifically inWonokromo and Wonolelo Village. This sub regency had the highest housing destruction in BantulRegency due to earthquake in 2006. This research aimed to understand the influencing factors of housing quality post-earthquake in the research area. Method used was survey method i.e.structured interview with 60 respondents in both villages and in-depth interview with key informants. Data was processed and analyzed inferentially statistic and qualitative descriptive. The result of this research is a difference in housing quality in both villages after earthquake. This difference occurs under the influence of internal and external factors. Internal factor includes citizen’s social and economic status which takes role in housing quality change in WonokromoVillage. Meanwhile, external factors involve financial support for housing rehabilitation and